A model for enhanced pea seedling vigour following low pH and salicylic acid treatments - Mccue, P.; Zheng, Z.; Pinkham, J.L.; Shetty, K.
In the simplest of terms, seed vigour is a visual measure of a seed's ability to germinate and survive its early growth and development period. Improvement of seed vigour is important for optimal emergence, stress resistance and uniform growth of emerging seedlings. We have hypothesized that acid-induced cell growth and elongation is regulated through the pentose-phosphate pathway; therefore, the effect of acidification linked to salicylic acid (SA)on growth, cell elongation, and phenolic synthesis was investigated. The experiments consisted of low pH and SA treatments followed by the measurement of phenolic levels and assay of the key regulatory enzyme of the pentose-phosphate pathway, glucose-6-phosphate dehydrogenase (G6PDH), and guaiacol peroxidase (GPX), during post-germination growth and elongation of peas. Phenolic and enzyme levels were determined by UV spectrophotometric assays. A low pH environment stimulated phenolic synthesis and increased tissue rigidity. Stimulating phenolic synthesis through low pH treatment supports the hypothesis that acid-induced cell growth and elongation may be regulated through the pentose-phosphate pathway. Based on concomitant stimulation of G6PDH and increase in proline content, the pentose-phosphate pathway may be linked to stimulation of proline metabolism in response to the above treatments. It has been hypothesized that this pathway produces the critical precursors for the synthesis of phenolic secondary metabolites that are important for plant growth and lignification.
Keywords: PROLINE; VIGOUR; ACIDIFICATION; G6PDH; NADPH2; PHENOLICS; CELL ELONGATION